Acellular dermal matrix used after large surgical ressection in ameloblastoma with buccal mucosa extension: a case report - Jácome-Santos, Humberto (2021)
Neoplastic, traumatic, and inflammatory diseases of the oral cavity and oropharynx frequently result in significant defects after resection, also, they may present challenge reconstruction. Regional and distant flaps such as skin grafts (SGs) are routinely used to cover mucosal defects arising from large resections, to restore tissue volume and preserve function. However, there are some disadvantages, mainly related to the donor site morbidity, including pain, risk of infection, occasional hypertrophic scar, and additional contracture resulting from a relative lack of dermis. Therefore, acellular dermal membrane (ADM) seems to be an applicable option to avoid those issues, and it has been shown good results for covering tissue defects. Thus, this study reports the first experience of using the double-layer dermal substitute (DLDS) (NeveliaÒ made by Symatese, France) in oral cavity, to cover and repair a buccal defect, immediately after a large resection of ameloblastoma extending to buccal mucosa. After surgical intervention and actually in follow-up, the patient shows good aesthetic and functional status, 24 months postoperatively. Thus, this DLDS seems to be a good resource in primary buccal reconstruction after extensive tumor resection. However, more studies are needed to be performed.